Value Added and Profitability Analysis of Innovative Seaweed Buoy Production in North Kalimantan - Banyuriatiga; Khaerunnisa; Andri Yogi Adyatma Prasetyo (Jurnal Manajemen Bisnis, 2026)
Seaweed cultivation requires supporting facilities, including buoys to maintain the stability of cultivation lines in marine waters. In coastal areas of Nunukan, discarded plastic bottles and shrimp feed containers are widely used as buoy materials, contributing to marine plastic waste accumulation. This study employed a single case study approach focusing on a pioneer entrepreneur producing recycled seaweed buoys in Mamolo, Southern Nunukan. The research aimed to analyze the value added and profitability of this business. Data were obtained from one respondent who actively manages buoy production, and the Hayami method was applied to estimate value added from processing plastic waste into seaweed buoys. The results showed that value added reached Rp 47,702.70. Margin distribution indicated that 2.83% was allocated to labor income, 10% to other inputs, and 87.22% to entrepreneur profit. The Margin of Safety was 75.08%, the MIR was 49.26%, and profit reached 36.99%, demonstrating both economic and environmental potential.